2016
DOI: 10.1080/09546634.2016.1227420
|View full text |Cite
|
Sign up to set email alerts
|

Predicting therapy response to mycophenolic acid using UGT1A9 genotyping: towards personalized medicine in atopic dermatitis

Abstract: Atopic dermatitis (AD) is a very common chronic inflammatory skin disease requiring long-term treatment. Mycophenolic acid (MPA) is used off-label in treatment of patients with severe AD failing Cyclosporin A (CsA) treatment, however clinical efficacy is observed in only half of the AD patients. In blood, MPA levels are known to have a large interindividual variability. Low MPA exposure and increased enzyme activity correlates with the presence of UGT1A9 polymorphisms. In this retrospective study, 65 adult AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
9
0
2
Order By: Relevance
“…MMF and mycophenolate sodium inhibit purine synthesis in B and T lymphocytes by directly inhibiting inosine monophosphate dehydrogenase 54. The overall efficacy of MMF is dependent on a UGT1A9 polymorphism that ultimately affects the metabolism of MMF 55. In a 2017 study assessing UGT1A9 enzyme activity and MMF bioavailability, 85% of subjects who carried the UGT1A9 polymorphism were MMF nonresponders, presumably due to a suboptimal exposure to MMF 55.…”
Section: Treatmentsmentioning
confidence: 99%
“…MMF and mycophenolate sodium inhibit purine synthesis in B and T lymphocytes by directly inhibiting inosine monophosphate dehydrogenase 54. The overall efficacy of MMF is dependent on a UGT1A9 polymorphism that ultimately affects the metabolism of MMF 55. In a 2017 study assessing UGT1A9 enzyme activity and MMF bioavailability, 85% of subjects who carried the UGT1A9 polymorphism were MMF nonresponders, presumably due to a suboptimal exposure to MMF 55.…”
Section: Treatmentsmentioning
confidence: 99%
“…Conversely, MMF was successfully used as long-term treatment (1–2 g daily over 12–29 months) in three patients with a chronic form of atopic eczema [ 85 ]. A recent retrospective study demonstrated that there was a direct correlation between UGT1A9 polymorphisms and MPA therapy unresponsiveness in patients with AD [ 86 ]. The main side effects reported during MPA therapy were nausea, fatigue, flu-like syndrome and liver enzyme alteration [ 80 , 87 , 88 ].…”
Section: Methodsmentioning
confidence: 99%
“…Für die topische Applikation stehen dabei Glukokortikoide (TGK) [6] in unterschiedlichen Wirkstärken, mit einem variablen therapeutischen Index [7,8] und in unterschiedlichen Galeniken sowie verschiedene Calcineurininhibitoren (TCI) [9] zur reaktiven und proaktiven Therapie zur Verfügung. In der Systemtherapie können in Ausnahmefällen Glukokortikoide (SGK), indikationsgerecht Ciclosporin (CSA) [10] oder Dupilumab [11], und als Off-label-Therapien Methotrexat (MTX) [12,13], Azathioprin (AZA) [14][15][16][17] oder Mycophenolsäurederivate (MPA) [18] eingesetzt werden. Für ein chronisches Handekzem im Rahmen des atopischen Syndroms kann auch eine Therapie mit Alitretinoin (ALI) erwogen werden [19].…”
Section: Handlungsempfehlung Zur Therapieumstellung Von Immunsuppressunclassified